Avaliação do desempenho da estação de tratamento de esgoto de Pirapora-MG e do acúmulo de lodo na lagoa de polimento em operação por treze anos - Valim, Patrick Cláudio Nascimento (2022)
Polishing ponds are used to complement the removal of organic matter from anaerobic reactors, in addition to removing of nutrients and pathogenic organisms. During its operation, solids settle, constituting the sludge. As this treatment by-product accumulates, there is a gradual reduction in the useful volume of the pond, so that there may be a reduction in performance over time and a change in the hydrodynamics of the reactor. For this reason, this material needs to be removed periodically, a practice that is not foreseen in the design of many Wastewater Treatment Plants (WTP) and/or is not included in the unit's maintenance routine. Thus, the objective was to evaluate the accumulation of sludge in the polishing pond and the performance of the Pirapora’s Wastewater Treatment Plant, in operation for thirteen years, and which is composed of preliminary treatment, UASB reactor and polishing pond. The accumulated sludge was characterized quantitatively, by bathymetry made using rods and PVC disk, and qualitatively, with collections in 6 sections, to determine the contents of total solids (TS), suspended solids (SS), volatile solids (VS), fixed solids (FS), total Kjeldahl nitrogen (TKN), total phosphorus (TP), pH and helminth eggs. The analysis of the hydrodynamics of the polishing pond was carried out with the aid of a drogue loaded with a smartphone, in addition to the use of green coconuts (use as floats) in an additional evaluation. Finally, in order to infer the existence of any trend of performance loss over the period of operation, a statistical evaluation of the historical series of analyzes of the plant (use of data from routine bimonthly monitoring of the WTP) was carried out. Based on the results, it was observed that there was a greater accumulation of sludge near the center of the pond, in the same alignment of the effluent inlet and outlet devices, forming an "island" of 10,968 m³, which reduced the theoretical hydraulic retention time (HRT) of 9,62 to 6.52 days. In the hydrodynamic test, the drogue made a trajectory towards the left side of the polishing pond, after the inlet pipe, possibly due to the influence of the “island” of accumulated sludge and the prevailing wind direction. The highest concentration of the series of solids, phosphorus, TKN and helminth eggs, and addition to the highest pH value, are found in section # 5, notably the site of greatest sludge accumulation. As this is the region of the pond where there is also the highest VS/TS ratio, this is another indication that it is the most recent site of sludge accumulation, with the sedimentation rate being higher than the degradation rate. Evaluating the historical series, it was verified that there’s no trend of loss of performance of the WTP. The efficiencies for the variables BOD, COD, Escherichia coli, phosphorus, ammoniacal nitrogen and sedimentable solids increased numerically, although, with no statistical differences in recent years, even with higher quantity of accumulated sludge. Thus, it can be concluded that the accumulated sludge reduced the theoretical HRT and influenced the hydrodynamics, but there was no perceptible interference (statistical tests and descriptive statistics) in the WTP performance regarding the removal of the studied variables.